THE ERA OF SOCIETY 5.0 AND IT’S CHALLENGES FOR ISLAMIC RELIGIOUS EDUCATION TEACHERS - Putri, Ulfi Annisa (Prodi Pendidikan Agama Islam STAI Darul Falah, 2024)
Teachers are one of the components of education and have a big role in determining the success or failure of the objectives of school subjects, including Islamic religious education. The teachers must create an appropriate teaching and learning process because they are responsible for helping students not only acquire knowledge but also develop interests and meet learning goals. After experiencing the industrial era 4.0, researchers are amazed by the changes that have occurred in the era of society 5.0. This research aims to know deeply about the era of society 5.0 and its challenges for Islamic religious education teachers. Library research was the method applied in this research. As the results, it was found that there are several challenges that are faced by the Islamic religious education teachers in the era of society 5.0. These challenges include the quality of education, advances in technology & digitalization, the digital divide, and the role & identity of teachers.